Integrated omics approach to unveil antifungal bacterial polyynes as acetyl-CoA acetyltransferase inhibitors - Ching-Chih Lin; Sin Yong Hoo; Li-Ting Ma; Chih Lin; Kai-Fa Huang; Ying-Ning Ho; Chi-Hui Sun; Han-Jung Lee; Pi-Yu Chen; Lin-Jie Shu; Bo-Wei Wang; Wei-Chen Hsu; et al. (Communications Biology, 2022)
In a multi-omics analysis, bacterial polyynes are found to act as antifungal agents by inhibiting the Candida albicans polyyne resistance gene ERG10, the homolog of MasL encoding acetyl-CoA acetyltransferase.